Effect of high CO2 and ocean acidification on photosynthesis and response to oxidative stress in seagrasses - Costa, Monya Mendes (2014)
Climate change scenarios comprise significant modifications of the marine realm, notably ocean acidification and temperature increase, both direct consequences of the rising atmospheric CO2 concentration. These changes are likely to impact marine organisms and ecosystems, namely the valuable seagrass-dominated coastal habitats. The main objective of this thesis was to evaluate the photosynthetic and antioxidant responses of seagrasses to climate change, considering CO2, temperature and light as key drivers of these processes. The methodologies used to determine global antioxidant capacity and antioxidant enzymatic activity in seagrasses were optimized for the species Cymodocea nodosa and Posidonia oceanica, revealing identical defence mechanisms to those found in terrestrial plants. The detailed analysis and identification of photosynthetic pigments in Halophila ovalis, H.stipulacea, Zostera noltii, Z marina, Z. capricorni, Cymodocea nodosa and Posidonia oceanica, sampled across different climatic zones and depths, also revealed a similarity with terrestrial plants, both in carotenoid composition and in the pigment-based photoprotection mechanisms. Cymodocea nodosa plants from Ria Formosa were submitted to the combined effect of potentially stressful light and temperature ranges and showed considerable physiological tolerance, due to the combination of changes in the antioxidant system, activation of the VAZ cycle and accumulation of leaf soluble sugars, thus preventing the onset of oxidative stress. Cymodocea nodosa plants living in a naturally acidified environment near submarine volcanic vents in Vulcano Island (Italy) showed to be under oxidative stress despite the enhancement of the antioxidant capacity, phenolics concentration and carotenoids. Posidonia oceanica leaves loaded with epiphytes showed a significant increase in oxidative stress, despite the increase of antioxidant responses and the allocation of energetic resources to these protection mechanisms. Globally, the results show that seagrasses are ...